Analysis of water use by gated communities in South Africa - Du Plessis, Jacques; Jacobs, Heinz (Water S. A., 2018)
Gated communities (hereafter GCs) are popular in many countries, including South Africa, because added security and lifestyle improvements are offered relative to homes built on freestanding properties. One of the key factors for the popularity of GCs is the availability of amenities to support the demands of the residents, such as gymnasia, walkways, golf courses, play parks and polo fields. Further benefits include the improved management of infrastructure such as telecommunication services, roads, water, sewer, electrical and stormwater assets. GCs are often governed by trustees or homeowners’ associations, responsible for the operation and the maintenance functions of the infrastructure, as well as implementing and adhering to legislation that pertains to the GC. As part of this study, the monthly water-use records of 2 888 GCs in 3 different South African cities were analysed. Water use was evaluated for each GC as a whole, and also per household in each case. The average number of homes per GC was 33 households/GC, with the smallest GC in the study sample containing 3 houses and the largest 524 houses. One of the study sites was in the winter rainfall region, while 2 sites were in the summer rainfall region. The average annual water use of individual households in each GC was plotted against current guidelines and was found to be relatively low. The average annual daily demands of all properties in the winter rainfall region was 0.63 kL/d, compared to 0.66 kL/d and 0.49 kL/d for the two study sites in the summer rainfall region. The results highlighted peculiarities in the water use of GCs that have not been reported on before, in particular the relatively low water use and the differences between GC homes’ water use in the various rainfall regions.